Violence and mental disorder: clinical considerations - Kennedy, Harry (Seminars in forensic psychiatry, 2024)
Violence is common and is a public health issue. Forensic psychiatrists offer treatment for the small amount of violence that is due to mental disorder. It is essential to distinguish between meaningful explanations and causes. Violence is not a unitary concept. Evidence for the specific causal associations between mental illness and violence is reviewed. Anger, anxiety, moral and amoral actions are reviewed including intoxication and withdrawal, deception, antisocial personality and psychopathy, and a range of mental illnesses and developmental disorders. Social and developmental factors are also important. Memes, media and social contagion influence the forms of violence. Court reports and treatments are considered critically in relation to violence.